Characterization of Immune Responses Induced by Ebola Virus Glycoprotein (GP) and Truncated GP Isoform DNA Vaccines and Protection Against Lethal Ebola Virus Challenge in Mice - Li, Wenfang; Ye, Ling; Carrion, Jr, Ricardo; Mohan, Gopi S; Nunneley, Jerritt; Staples, Hilary; Ticer, Anysha; Patterson, Jean L; Compans, Richard W; Yang, Chinglai (The Journal of infectious diseases, 2015)
In addition to its surface glycoprotein (GP), Ebola virus directs the production of large quantities of a truncated glycoprotein isoform (sGP) that is secreted into the extracellular space. We recently reported that sGP actively diverts host antibody responses against the epitopes that it shares with GP and thereby allows itself to absorb anti-GP antibodies, a phenomenon we termed "antigenic subversion." To investigate the effect of antigenic subversion by sGP on protection against virus infection, we compared immune responses induced by different prime-boost immunization regimens with GP and sGP DNA vaccines in mice and their efficacy against lethal Ebola virus challenge. Similar levels of anti-GP antibodies were induced by 2 immunizations with sGP and GP DNA vaccines. However, 2 immunizations with GP but not sGP DNA vaccine fully protected mice from lethal challenge. Boosting with sGP or GP DNA vaccine in mice that had been primed by GP or sGP DNA vaccine augmented the levels of anti-GP antibody responses and further improved protective efficacy against Ebola virus infection. These results show that both the quality and the levels of anti-GP antibody responses affect the efficacy of protection against Ebola virus infection.